Modern Slavery Prevention and Responses in South Asia: An Evidence Map - Oosterhoff, Pauline; Yunus, Raudah; Jensen, Charity; Somerwell, Francis; Pocock, Nicola (DFID, 2018)
The Asia Pacific region has the highest numbers of both slavery and ch ild labour victims in the world. The International Labour Organization (ILO) estimates that 16.5 million and 8.4 million persons were in sit uations of forced labour and forced marriage respectively in Asia Paci fic, among 40.3 million in modern slavery globally (ILO & Walk Free Fo undation 2017). Although there is a growing body of research and evalu ations on specific sub-sectors and interest in the worst forms of labo ur exploitation, there has not yet been a systematic scoping or synthe sis of studies that would help policymakers understand ‘what works’ to reduce the prevalence of “Modern Slavery”2(MS) in the countries of in terest to DFID (India, Nepal, Bangladesh, Pakistan). India alone is es timated to have the largest number of people in modern slavery in the world with nearly 8 million persons living in modern slavery, followed by 3.2 million, 592,000 and 171,000 in Pakistan, Bangladesh and Nepal respectively (Walk Free Foundation 2018). While systematic reviews on interventions to reduce prevalence of trafficking, forced or bonded l abour or slavery exist, these have not focused on the target countries of interest to DFID. Previous systematic reviews have focussed on par ticular types of MS, such as cross border sexual exploitation globally (van der Laan et al. 2011), labour exploitation in Europe (Cockbain e t al. 2018) or community based interventions for safer migration progr amming in low and middle income countries (LMICs) (Zimmerman et al. 20 16). Several systematic reviews focus specifically on health needs and post-trafficking care or interventions (Ottisova et al. 2016; Muraya & Fry 2016; Hemmings et al. 2016; Dell et al. 2017), and research meth ods and tools used in trafficking in persons (TIP) and health research (Cannon et al. 2018; Doherty et al. 2016). A recent global review and evidence map of MS interventions found some interventions in the targ et countries, but the outcomes were not specified (Bryant & Joudo 2018 ). In this Evidence Map, we address this gap in evidence for India, Ne pal, Bangladesh and Pakistan specifically, scoping the range of Modern Slavery interventions and outcomes for specific target populations (s urvivors, employers, landlords, services providers, criminal justice o fficials) and at different levels (individual, community, state). This map is foremost targeted to DFID and its partners in India, Nepal, Ba ngladesh and Pakistan to inform evidence-based policy making. We hope that it is also useful to academics and practitioners working to addre ss modern slavery, or in intervention areas or locations described.